Pengaruh Pendapatan Orang Tua, Literasi Keuangan, dan Gaya Hidup Terhadap Pengelolaan Keuangan Pribadi Siswa SMKN 6 Surabaya - Zakiyah, Fitrohtus; Listiadi, Agung (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze whether there is a simultaneous influence between parental income, financial literacy, and lifestyle on the personal financial management of students at Vocational High School 6 Surabaya, to analyze whether there is an influence between parental income on the personal financial management of students at SMKN 6 Surabaya, to analyze Is there an influence between financial literacy on the personal financial management of Vocational High School 6 Surabaya students, and to analyze whether there is an influence between lifestyle on the personal financial management of Vocational High School 6 Surabaya students. The respondents in this research were class X students majoring in financial and institutional accounting at Vocational High School 6 Surabaya, totaling 72 respondents. The sampling technique used in this research is saturated sampling. Data collection techniques use questionnaires and tests. The results of this study indicate that (1) Parental income, financial literacy, and lifestyle simultaneously influence the personal financial management of S Vocational High School 6 Surabaya students (2) Parental income significantly influences the personal financial management of Vocational High School 6 Surabaya students (3) Literacy finances have a significant influence on the personal financial management of Vocational High School 6 Surabaya students (4) Lifestyle has a significant influence on the personal financial management of Vocational High School 6 Surabaya students.